2003
DOI: 10.1002/sia.1626
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Al KLL Auger spectra of oxidized aluminium foils

Abstract: Threshold Al KLL Auger electron spectroscopy and K-edge x-ray absorption fine structure spectroscopy have been used to examine technical purity (99.5%) aluminium foil before and after chemical treatment that altered the thickness and degree of hydroxylation of the oxidized layer. Comprehensive surface chemical characterization was effected by means of monochromatized Al Ka-excited photoelectron spectroscopy. Threshold Al KL 2,3 L 2,3 spectra were obtained for three of the foils investigated and these spectra w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…However, our firstprinciples results for pure metallic Al agreed well with the experimental data, although the present experimental line shapes showed spectral features similar to those described in the previous report. 17) From the results of our present calculations, it is concluded that the main component of the present Al K-edge spectrum of metallic Al measured by the TEY method was bulk metallic Al. In the case of AlN, peak E was missing in the theoretical spectra obtained with the 3 Â 3 Â 1 supercell, although this supercell provided better agreement with the experimental data than the smaller 2 Â 2 Â 1 supercell.…”
Section: Ev (áE=e ¼ þ0:3%)mentioning
confidence: 51%
See 3 more Smart Citations
“…However, our firstprinciples results for pure metallic Al agreed well with the experimental data, although the present experimental line shapes showed spectral features similar to those described in the previous report. 17) From the results of our present calculations, it is concluded that the main component of the present Al K-edge spectrum of metallic Al measured by the TEY method was bulk metallic Al. In the case of AlN, peak E was missing in the theoretical spectra obtained with the 3 Â 3 Â 1 supercell, although this supercell provided better agreement with the experimental data than the smaller 2 Â 2 Â 1 supercell.…”
Section: Ev (áE=e ¼ þ0:3%)mentioning
confidence: 51%
“…In the case of metallic Al, the agreement between the experimental and calculated spectral profiles was slightly improved by increasing the supercell size. The previous report 17) mentioned that the XANES profile of metallic Al mainly originated from Al oxides and/ or hydroxides when it was measured by the TEY method, which was the main reason why the spectral profiles differed between the TEY and TFY methods. However, our firstprinciples results for pure metallic Al agreed well with the experimental data, although the present experimental line shapes showed spectral features similar to those described in the previous report.…”
Section: Ev (áE=e ¼ þ0:3%)mentioning
confidence: 99%
See 2 more Smart Citations
“…(peak f), ~1566 eV (peak g) and ~1568 eV (peak h) originate from aluminium bonded to oxygen in either a disordered octahedral (peaks f and h) or tetrahedral (peak g) arrangement [36,37]. The peak located at 1571 eV (peak i) is due to multiple scattering events [38].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%